PENERAPAN TEKNOLOGI SPINNER UNTUK MENINGKATKAN PRODUKSI MINUMAN BUBUK JAHE INSTAN DI UKM AR-RIDWAN KOTA PADANG - Sri mutiar; Ruri Wijayanti; Dewi Arziyah; Lisa Yusmita; Malse Anggia; Ariyetti Ariyetti (Jurnal Hilirisasi IPTEKS, 2023)
Instant spice drinks that function to maintain body stability and are believed to be able to increase the body's immunity are developing very rapidly in the era of the Covid-19 pandemic. Ginger is a spice with various benefits, providing opportunities for the Small Business industry. One of them is the instant spice drink industry player "Instant Red Ginger Ar-ridhwan" which produces natural instant spice drinks. However, the processing of instant spice drinks still needs to be improved. In this case, appropriate technology is urgently required to speed up the production process. The purpose of this activity is to introduce technology in the production of instant spice drinks to produce products with more guaranteed quality and to be able to generate additional income for partners through the optimization of processing. The service begins with identification, planning, trial production of instant spice drinks, and evaluation. The stages of implementing this activity are socialization, demonstration/training, and evaluation. The results of the activities that have been carried out show new knowledge for partners in carrying out alternative applications of ginger processing technology, especially in the ginger squeezing process. The spinner tool can shorten ginger's pressing time compared to using the previous press tool. The application of appropriate technology in the production of instant spice drinks needs to be carried out thoroughly at every stage of the processing process to be able to increase the maximum quality and quantity, and product testing is required to produce products with more guaranteed quality and be able to generate additional income for partners and the community.